Pengaruh Jenis Pakan terhadap Kualitas dan Pertumbuhan Anak Ayam Kampung (Gallus Gallus Domesticus) - Munthe, Ratna Dewi; Nanda, Annisa Aulia; Lubis, Febrianti Putri; Hasibuan, Febry Rahmadhani (Lembaga Yasin AlSys, 2023)
Feed is food/intake given to livestock such as chickens. The type of feed for livestock greatly affects the quality and growth of these animals. Based on the above background, it is necessary to conduct a study, so that later it can be used as a basic reference regarding knowledge about the effect of types of chicken feed on the development of chicks in educational and research activities. Research data collection was carried out using the exploratory and observation method, namely tracing community chicken breeders and observing the chickens themselves. Identification and observation were also carried out in order to obtain primary data by direct observation of these animals. The results showed that the quality of chicks II was better than the quality of chicks I. Based on the research that had been done, it could be concluded that the results of the research were carried out by observing. In the first observation, the hens did not have too much type of feed, namely the feed was only ground corn. Whereas in observation II the hens were wild and the types of feed were more diverse, namely bran, rice, food waste and corn rice. In order to obtain data that the quality of the chicks to the observations of chicks I and the observations of chicks II is different.